(untitled) - Saveant, Jean Michel (Hoboken, N.J., 2006)
This book is based on the George Fisher Baker Lecture given by Jean-Michel Sav?ant at Cornell University in Fall 2002: The first book focusing on molecular electrochemistry. Relates to other fields, including photochemistry and biochemistry. Outlines clearly the connection between concepts, experimental illustrations, proofs and supporting methods. Appendixes to provide rigorous demonstrations to prevent an overload of algebra in the main text
Keywords: Electrochemistry,Charge exchange,Chemical kinetics,Điện hoá học,Trao đổi điện tích,Hóa động học